Construction of Mesoporous Frameworks with Vanadoborate Clusters1. Issue 14 (3rd March 2014) - Chen, Hong; Yu, Zheng‐Bao; Bacsik, Zoltán; Zhao, Huishuang; Yao, Qingxia; Sun, Junliang
Abstract A new porous vanadoborate was synthesized by employing the scale chemistry theory with the vanadoborate cluster V10B28. The twofold interpenetrated lvt network was assembled with zinc‐containing elliptical vanadoborate clusters and Zn polyhedra. The single lvt framework contains a three‐dimensional 38×38×20 ring channel system with the pore size (24.7×12.7 Å) reaching the mesoscale, thus indicating the possibility of constructing 3D ordered mesopores with vanadoborate clusters. The porosity of the SUT‐7 structure was confirmed by CO2 adsorption of the as‐synthesized materials.